Second-Year Students’ Perceptions Towards Learning News Vocabulary With Bbc News Review At Ufls, Ud (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
English is widely recognized as the world's leading language and serves as a universal medium of communication for people from different cultures and countries. Many universities in Vietnam, particularly the University of Foreign Languages in Da Nang, require students pursuing the English language to pass standardized tests such as the TOEFL or IELTS.... in order to graduate. These tests evaluate a student's English language proficiency, which includes a strong command of English vocabulary. Therefore, to succeed on these tests, students must have a thorough understanding of English vocabulary, as well as excellent reading, writing, speaking, and listening skills. Vocabulary is the basic foundation for a person to communicate as well as successfully learn English. Students will become more confident when they understand many English words. In the face of the various vocabulary sources, choosing suitable sources has become extremely necessary for studying English and improving vocabulary. The current study aims to explore the effectiveness of using BBC News Review as a tool for learning new vocabulary from the perspective of second language learners in Vietnam. The findings of this study can have important implications for language teachers and learners in Vietnam, as well as for educators in other contexts who are interested in using technology to support vocabulary acquisition.